PERANAN HAKIM DALAM PENEMUAN HUKUM (RECHTSVINDING) DALAM MENANGANI KASUS PERKARA - Nurindahwati, Zuhro (Jurnal Ilmiah Raad Kertha, 2025)
The law must be enforced and implemented, because the law serves as a protector of the interests of justice seekers, Law enforcement must pay attention to the elements of legal certainty, expediency and justice. Therefore, these three elements must be ensured and can be considered proportionally, so as to produce decisions that can uphold the law, judges are required to be able to impose decisions objectively and objective decisions are only achieved through legal discovery (Rechtvinding) by the Judge. Therefore, the role of judges in every stage of legal discovery activities (rechtvinding) to determine concrete events that actually occur is very important in achieving quality and fair decisions.